Life-style and metabolic factors do not affect risk for glioma: a prospective population-based study (The Cohort of Norway) - Gheorghiu, Anamaria; Brunborg, Cathrine; Johannesen, Tom B.; Helseth, Eirik; Zwart, John-Anker; Wiedmann, Markus K. H. (Frontiers in Oncology, 2024)
BackgroundThe identification of modifiable risk factors for intracranial glioma remains a significant challenge. While lifestyle factors and metabolic syndrome are well-established risk factors for various other cancers, their association with glioma risk remains unclear.ObjectivesThis study aims to conduct a comprehensive analysis of lifestyle factors and metabolic factors in relation to glioma risk.MethodsThe Cohort of Norway (CONOR) is a prospective, population-based health survey encompassing anthropometric measurements, blood tests and health questionnaires. CONOR data were linked to the National Cancer Registry to identify incident glioma cases. Follow-up time was calculated in person-years from the baseline examination until the date of glioma diagnosis, death, or the end of the follow-up period. Cox proportional hazards regression was used to calculate hazard ratios (HR).ResultsThe study cohort included 160,938 women and men. Over 2.8 million person-years of follow-up, 319 intracranial gliomas were diagnosed. Lifestyle factors such as physical activity, alcohol consumption, smoking, and marital status were not associated with glioma risk. There was no increased glioma risk among participants with diabetes mellitus or hypertension. Furthermore, metabolic syndrome in both women and men was not associated with an elevated risk of glioma. Blood lipids, including total cholesterol, triglycerides, and HDL, were not linked to glioma risk. However, increasing LDL levels were associated with a decreased risk of glioma in men (HR per category 0.84; 95% CI 0.74-0.96), but not in women.ConclusionThis is the first comprehensive prospective cohort study to evaluate potentially modifiable risk factors for glioma. Our findings do not support previously suggested associations between smoking, alcohol consumption, or metabolic syndrome and glioma risk.